Disseminated BCG as a unique feature of an infant with severe combined immunodeficiency - Norouzi, Sayna; Movahedi, Zahra; Mamishi, Setareh; Monajemzadeh, Maryam; Rezaei, Nima (The Turkish Journal of Pediatrics, 2011)
Severe combined immunodeficiency (SCID) is a rare primary immunodeficiency disease, which renders patients prone to recurrent severe infections in early childhood. Herein, we present a five-month-old boy with SCID who was referred to our center with recurrent diarrhea, respiratory infection and lymphadenopathy. Immunological studies showed hypogammaglobulinemia and low number of T-cells, which was compatible with the diagnosis of T- B+ SCID. An advanced cytomegalovirus pneumonitis was detected based on the results of lung necropsy. Cultures and polymerase chain reaction studies of bone marrow aspirates and spleen specimen were indicative of Mycobacterium bovis. This report emphasizes the importance of lymphadenopathy as a sentinel sign of immunological disorders. Underlying immunodeficiency diseases such as SCID should be considered in the differential diagnosis of an infant with infections and lymphadenopathy, particularly in the regions with routine national Bacillus Calmette-Guérin (BCG) vaccination.